ApoB100,LDLR-/- mice exhibit reduced electroretinographic response and cholesteryl esters deposits in the retina - Bretillon, Lionel; Acar, Niyazi; Seeliger, Mathias W; Santos, Mylène; Maire, Marie Annick; Juanéda, Pierre; Martine, Lucy; Grégoire, Stéphane; Joffre, Corinne; Bron, Alain M; Creuzot-Garcher, Catherine (Investigative ophthalmology & visual science, 2008)
To evaluate the retinal phenotype of 7- and 14-month-old apoB100,LDLR-/- mice, a relevant animal model of lipid metabolism dysfunction. Single-flash electroretinograms were obtained from 7- and 14-month-old apoB100,LDLR-/- and control mice fed a standard diet under both scotopic and photopic conditions. Visual cycle retinoids were analyzed in eyes from dark-adapted mice. Retinal and choroidal vascularization was evaluated with scanning laser ophthalmoscopy. Fatty acids were analyzed in the retina. Esterified and free cholesterol was detected in eye cryosections. Scotopic and photopic b-wave amplitudes were significantly reduced in apoB100,LDLR-/- mice compared with control mice at 7 and 14 months of age (between -25% and -35% in 7-month-old animals and between -50% and -60% in 14-month-old animals at 25 cds/m2). Esterified cholesterol was found to accumulate at the basement of the retinal pigment epithelium in apoB100,LDLR-/- mouse eyes. On the contrary, no significant changes in the retinal profile of fatty acids and visual retinoids were observed in apoB100,LDLR-/- mice compared with control animals. The exclusive expression of apoB100 in LDL receptor-null mouse altered the ERG profile, without modifying the visual cycle of retinoids and led to cholesterol deposition in the retina. These findings clearly suggest the role of cholesterol metabolism in the functioning of the retina and possibly in the etiology of ocular diseases, including age-related macular degeneration.